(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2024)
The present study was conducted on the volcanic soil of Mudja in Nyiragongo territory to evaluate the effect of fresh biomass of Tithonia diversifolia on the productivity of different potato varieties (Solanum tuberosum L.). The experimental set-up was a completely randomized block design with four replicates and three treatments. Tithonia leaves were incorporated into the soil two weeks before planting potato tubers at a quantity of 36 kg. The results showed that the general trend in plot productivity was in the order of : T3>T1>T2 with the Gahinga variety (T3) at 27.81T/ha. The study showed that Tithonia diversifolia, under the conditions of this trial, had great potential for improving soil nutrient availability and could supply the quantity of nutrients required for potato cultivation without using chemical fertilizers.